Pengenalan Metode Tilawati pada Jama’ah Pengajian Musholla Nurul Iman di Desa Mekar Sari Kecamatan Tanjung Raya Kabupaten Mesuji Provinsi Lampung - Afifah, Noor; Nopriansyah, Untung; Agustina, Irani; Adyan, Asyrofal; Hidayat, Ananda (Journal of Social Empowerment, 2024)
This article contains the results of research during the community service period in Mekar Sari Village, Tanjung Raya District, Mesuji Regency, Lampung Province.  Based on the results of observations when participating in the routine recitation activities of the Nurul Iman prayer room, there are several problems and one of them is the lack of interest in learning and reading the Koran by mothers in Mekar Sari village which is one of the problems that is the focus of this article's research.  The use of inappropriate methods in a lesson can cause learning outcomes to be less than optimal.  The application of the tilawati method is an alternative in increasing the motivation and ability of mothers to read the Qur'an.  The principle of teaching the Qur'an using the tilawati method is that it is taught practically using the rost song, taught in a classical manner, taught in groups with reading and listening techniques using the Al-Qur'an.  The implementation of Al-Qur'an learning using the tilawati method in the prayer congregation of the Nurul Iman musholla has had the effect of changing the ability of mothers to read the Al-Qur'an.  Supporting factors and inhibiting factors for learning the Qur'an with the tilawati method are influenced by technical and field conditions, as well as the conditions of the recitation congregation.  From this it is hoped that the interest and ability of the women in the prayer congregation at the Nurul Iman prayer room can increase so that learning outcomes are more effective and of good quality.